Effect of process variables in supercritical carbon dioxide extraction of tocotrienols from hydrolyzed palm fatty acid distillate (PFAD) - Othman, Najwa; Gun, H. Chong; M. Azman, Ezzat; Suleiman, Norhidayah (Wiley, 2022)
The recovery of tocotrienols from palm fatty acid distillate (PFAD), a by-product of palm oil, is of economic and environmental interest. In this study tocotrienols were extracted from PFAD using supercritical carbon dioxide (scCO2) at different temperatures (40–60°C) and pressures (20–40 MPa). The optimal process conditions were estimated to be 20 MPa and 53°C for 300 min and a CO2 flow rate of 32 ± 2 g/min, with 16.45 mg/g of tocotrienols extracted. Two modifications to the extraction process were then made at the optimal conditions. First, 180 min of static extraction was added before the dynamic extraction; and second, the solvent polarity was altered by adding 0.075 ml/g ethanol to the scCO2 system. These modifications significantly increased the tocotrienol extraction, to 23.62 mg/g and 30.03 mg/g, respectively. The use of scCO2 for the extraction of tocotrienols shows great potential, which might be extended to other compounds.